A Review: Exploring AI’s Role in Architecture: Redefining New Design Interactions - Ferdy Sabono (DIMENSI (Journal of Architecture and Built Environment), 2025)
The use of artificial intelligence in architecture has had a significant impact on the profession, sparking debate about its potential to fully automate architectural work. However, there is limited research on the influence of AI across all phases of the architectural design process. This article aims to analyze the extent of AI’s impact on architecture and to identify potential future benefits and challenges. The phases of architectural work discussed include pre-design, schematic design, design development, construction documentation, negotiation, and construction observation. Through a systematic literature review, this study highlights the transformative impact of AI across all stages of architectural design, emphasizing emerging concepts of design interaction and their implications for the profession. The findings suggest that while AI cannot fully replace architects, it indicates a shift in their role by enhancing collaboration and work flexibility. Nonetheless, the study emphasizes the importance of strengthening architects’ technological competence in using AI tools to ensure their continued relevance in the future.